SOCIO-ECONOMIC STATUS, GENDER AND TEACHERS' FACTORS AS PREDICTORS OF ACADEMIC ACHIEVEMENT IN ECONOMIC CONCEPT IN SOCIAL STUDIES - OMIYEFA, MURAINA OLUGBENGA (Indonesian Journal of Elementary Teachers Education, 2024)
The role of the teacher in the teaching-learning process is crucial for facilitating students’ learning.. However, there is a dearth of literature that incorporate socio-economic status such as parental (qualification, occupation, education, income), teachers' factors such as (qualification, work attitude and competence) and gender as they predict students’ academic achievement, particularly in economic concepts within the field of Social Studies. This study therefore investigated socio-economic status, gender and teachers' factors as predictors of students' academic achievement in economic concepts in Social Studies. The study adopted cross-sectional survey research design. Questionnaire was the instrument used to collect data from 350 respondents drawn from five senior secondary schools in Ibadan, Oyo State. Seventy students were selected each from the five schools drawn from Ibadan North local government areas of Oyo state. Data collected were analysed using chi-square and t-test at 0.05 level of significance. The result of the data analysis showed that there is prominent association between socio-economic status and students' academic achievement; there is significant relationship between teachers' factor and students' academic achievement and there is no significant relationship between academic achievement of male and female students in economic concepts in Social Studies. Based on the findings, it was recommended parents should improve the conditions of their home environment to suite the purpose of their children performing better in school work while teachers improve their method of instruction to address various personality traits of students.Keywords: Socio-economic status; Gender; Academic performance; Teacher’s factor